Modeling the Impact of Taxes on Petroleum Exploration and Development - Smith, James L. (International Monetary Fund, 2012)
We present a simple model of petroleum exploration and development that can be applied to study the performance of alternative tax systems and identify potential distortions. Although the model is a highly simplified, it incorporates many factors and some of the key tradeoffs that would influence an investor's investment behavior. The model recognizes the role of enhanced oil recovery and treats the impact of taxation on exploration and development in an integrated manner consistent with an investor's joint optimization of investments at both stages of the process. The model is simple and user-friendly, which facilitates application to a broad range of problems